HARMONIZATION OF TREATMENT APPROACHES: DRAWING INSPIRATION FROM PEDIATRIC TREATMENTS IN ADULT ACUTE LYMPHOBLASTIC LEUKEMIA THERAPY - Ferda Can (Hematology, Transfusion and Cell Therapy)
Age, genetic characteristics, comorbidities, and minimal residual disease determine prognosis in patients with Acute Lymphoblastic Leukemia (ALL). Advanced age, the presence of adverse genetic markers and reduced treatment intensity typically lead to poorer outcomes, with disease-free survival and remission rates decreasing with age. In adult patients, disease remission rates are around 35%. In recent years, there has been a growing focus on applying treatment protocols developed for pediatric age groups to adult ALL patients. In pediatric ALL protocols, the main factor that enhances treatment success is the dose intensity. These protocols involve higher doses and more frequent dosing intervals of L-asparaginase, vincristine, methotrexate and steroids compared to adult ALL protocols.In recent years, it has been shown that treatment regimens applied to young adult/adolescent ALL patients have an independent impact on outcomes. Various retrospective studies have shown that complete response rates in the 15-20 age group were similar between adult and pediatric protocols, but disease-free survival was significantly higher with pediatric protocols. There is no consensus about age range for the young adult/adolescent group. In some protocols, these protocols can be applied up to the age of 35 to 50 years. Rather than age, the intensity of chemotherapy can be determined according to patients' comorbidities and performance status.Current guidelines recommend pediatric-based chemotherapy protocols for young adult/adolescent patients with no comorbidities. These protocols include CALGB 10403, DFCI Protocol 00-01 and PETHEMA ALL-96. According to the prospective study results using the CALGB 10403 protocol, for ALL patients aged 17-39 years, the median event-free survival (EFS) was 78.1 months (historical control: 30 months); the 3-year EFS was 59%; and the median overall survival (OS) was not reached. The estimated 3-year OS was 73%, with a low treatment-related mortality rate of 3%.In a study by the Dana-Farber Cancer Institute (DFCI) group in adult ALL patients aged 18-50 using pediatric-based chemotherapy protocols, 85% of patients achieved complete remission (CR) after one month of intensive induction therapy. With a median follow-up of 4.5 years, the 4-year disease-free survival (DFS) for patients who achieved CR was 69%, and the 4-year OS was 67%.In the PETHEMA group's data for ALL patients aged 15-30 treated with a pediatric-based chemotherapy protocol, the CR rate was 98%. The 6-year EFS and OS were 61% and 69%, respectively.Other protocols recommended for ALL patients under 65 include the dose-adjusted CALGB 8811 Larson, MRC UKALLXII/ECOG 2993, GRAALL-2005, dose-adjusted HyperCVAD, USC/MSKCC ALL regimen based on the CCG-1882 regimen and the Linker 4-drug regimen. Studies using these protocols, CR rates were reported between 85% and 95%. Median survival was 36 months, with 3-year OS ranging from 50% to 70%, and 5-year OS ranging from 30% to 40%. Chemotherapy-related mortality is reported at approximately 5%.In conclusion, pediatric-based chemotherapy protocols offer higher CR rates compared to low-intensity treatments. Despite the lack of a significant increase in treatment-related mortality, the advantage of prolonged OS means that pediatric-based chemotherapy should be applied to all eligible adult ALL patients, whenever appropriate.